LOKAVAJJA AND BUDDHIST MONKS’ SAMAṆASĀRUPPA DEVELOPMENT - Piyapanyawong, Anchalee (Journal of MCU Nakhondhat, 2023)
This research paper aims to: 1) study the concept of Lokavajja in Theravada Buddhism, and 2) present considerations before proceeding to criticize Buddhist monks. This study is Documentary Research. Its main focuses are on collecting and analyzing the data obtained from primary and secondary documents which relate to Lokavajja. The study found that the concept of Lokavajja in Theravada Buddhism, the term “Lokavajja” is composed of 2 implications: Worldly Fault and Action Blamable by the Layman. The former is to consider the laws and social rules that are clearly enacted and thus can be easily used to consider the actions of Buddhist monks. On the other hand, the latter can be complicated to be considered. This might be because each person may consider a Buddhist monks’ action variously owing to employing his or her own criteria, criticizing them with prejudice and bad volitions. Therefore, those remarks are not truly helpful for the Buddhist monks’ samaṇasāruppa development. However, in the Buddha era, the Buddha used criticism to improve the Buddhist monks’ samaṇasāruppa and he had attached great importance to public reproach. In addition, the study also found that a truly useful reprimand for the Buddhist monks’ samaṇasāruppa development is composed of 5 elements as follows: 1) the censure corresponds to the facts, 2) the blamer has an intensive knowledge of precepts and practical traditions of Buddhist monks, 3) the blamer knows the basic criteria for considering of the Buddhist monks’ samaṇasāruppa, 4) the blamer has good intentions and does not prejudice towards the Buddhist monks, and 5) the method of censure must not cause the blamer to sin.